2016
DOI: 10.1021/jacs.6b11418
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Photocatalysts for Enantioselective Aerobic Oxidation of β-Ketoesters

Abstract: A novel visible-light-responsive chiral ligand has been developed by grafting a triplet state photosensitizer to chiral bisoxazoline ligands. Complexation of this ligand with Ni(acac) results in a powerful catalyst for the asymmetric oxidation reaction of β-ketoesters, which uses oxygen or air as the green oxidant and visible light or sunlight as the ideal driving force. Using this protocol, products containing the α-hydroxy-β-dicarbonyl motif are produced in high yields and with excellent enantiopurities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
88
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(93 citation statements)
references
References 75 publications
0
88
0
5
Order By: Relevance
“…[1] Photoredox catalysts,f requently Ir or Ru coordination complexes,u ndergo photoexcitation with visible light and can then either oxidize or reduce organic substrates through outersphere single-electron transfer (SET). [4,5] Fu, Peters,a nd co-workers have demonstrated in situ assembly of copper catalysts that effect alkylation of N, O, and Sn ucleophiles under visible-light irradiation (Scheme 1B). [2,3] Here,a si nc onventional PRC,t he photoredox catalyst is operating with the single function of outersphere SET.Analternative approach to dual catalytic chemistry would be to exploit the inner coordination sphere of photoredox catalysts,t oc apture as econd catalytic activity from the same metal center.…”
mentioning
confidence: 99%
“…[1] Photoredox catalysts,f requently Ir or Ru coordination complexes,u ndergo photoexcitation with visible light and can then either oxidize or reduce organic substrates through outersphere single-electron transfer (SET). [4,5] Fu, Peters,a nd co-workers have demonstrated in situ assembly of copper catalysts that effect alkylation of N, O, and Sn ucleophiles under visible-light irradiation (Scheme 1B). [2,3] Here,a si nc onventional PRC,t he photoredox catalyst is operating with the single function of outersphere SET.Analternative approach to dual catalytic chemistry would be to exploit the inner coordination sphere of photoredox catalysts,t oc apture as econd catalytic activity from the same metal center.…”
mentioning
confidence: 99%
“…[8] The sequential acylation/reduction operation afforded am ethylated diamine 2a;f urthermore,t he condensation of odiaminobenzene derivative 3a and ethyl chloroacetate provided chloromethyl-substitutedb enzimidazole 4a.T he subsequent alkylation of 2a with 4a under basic conditions gave an ew chiral N 4 ligand L1.F inally,c oordination of L1 with CoCl 2 ·(H 2 O) 6 in CH 3 CN completed the synthesis of designed chiral octahedral complex DCo1,which was confirmed by Xray crystallographic analysis. [9] As part of our ongoing research interest in visible-lightinduced asymmetric photochemical reaction, [10] we planned to examine the catalytic performance of the well-defined Co complex, DCo1,a sachiral Lewis acid catalyst in the benchmark photo-Giese reaction (conjugated addition to electron-deficient alkenes by photogenerated radicals). [11,12] Initially,w el aunched this study by using enone 5a and 4benzyl-substituted Hantzsch ester (HE) 6a as model substrates and Mes-AcrClO 4 (PC)a sap hotocatalyst under irradiation of two 3Wblue LEDs.I nt he presence of chiral Co catalyst, chiral ketone 7a was produced in good yield with moderate enantioselectivity (Table 1, entry 1: 80 %y ield, 70:30 e.r.…”
mentioning
confidence: 99%
“…As shown in Figure 2, the coordination of achiral diamine unit with aCocenter, though being favored to induce the chirality of the metal center, makes the steric tert-butyl groups distant from the plane comprising of Co,C l, and O atoms (S LCo1 = 5.05 vs.S LRh1 = 4.57 ). According to above analysis,w es peculated that the adjustment of the 5-position of benzimidazole would help to improve the enantioselectivity.T hus,f ollowing the same synthetic route of DCo1,c hiral Co complexes DCo2-4 were facilely prepared and tested using the model reaction ( 10), and replacement of the central metal Co with other 3d metals (that is,Mn, Fe,Ni, Cu, and Zn), 4d metals (that is,Ru and Rh) or the 5d metal Ir,o nly results in lower or even no enantioselectivity (see the Supporting Information for details). Presumably,both of these two structural characteristics would be unfavored for the stereoinduction capacity of LCo1.…”
mentioning
confidence: 99%
“…Initial optimization studies revealed that using ac atalytic amount of phosphoric acid [(R)-BPA 3c as ac atalyst with 2equiv PinBH as ar eductant in dry 1,4dioxane] under irradiation of purple LEDs (395 nm) for 2hours under ambient atmosphere gave the best yield for the desired product 2a (entry 1). Lower yields were observed when using K 2 HPO 4 ,H 3 PO 4 (3a), or diphenylphosphinic acid (3b)a sc atalysts (entries [2][3][4][5]. Lower yields were observed when using K 2 HPO 4 ,H 3 PO 4 (3a), or diphenylphosphinic acid (3b)a sc atalysts (entries [2][3][4][5].…”
Section: Resultsmentioning
confidence: 99%